ePortfolios and the Development of Student Career Identity Within a Community of Practice: Academics as Facilitators and Guides - Bennett, Dawn; Robertson, Rachel (2017)
Based on the position that ePortfolios are a mode of innovative practice that benefits pedagogical thinking and action, this chapter investigates educators’ roles as facilitators in the process of ePortfolio development. It is based on the authors’ experience with final-year writing students, whose simultaneous ePortfolio development, industry placement, career-focussed workshops and online blogs provided unique opportunities for students and staff to explore students’ imminent transition into the workforce. This project saw students negotiate their identities within what became a blended learning community of practice. As members of this community the authors found themselves as facilitators and guides rather than teachers. Reflections, blog posts and ePortfolios formed a dataset from which this setting could be analysed from pedagogical and scholarly perspectives. Within the chapter, findings from the project are presented, and its characteristics that led to a mediated environment in which students developed self and career identities through their ePortfolio thinking are investigated. Key findings were twofold. First, the ability to “experience” multiple workplaces through their online interactions with peers led students to develop a broader preview of their future selves and to develop their ePortfolios in line with these possibilities. Second, the group process and modelling of community of practice behaviours fostered complex reflective thinking skills in individual students.